DOCKING AMPRENAVIR DAN SENYAWA TURUNANNYA SEBAGAI ANTI-HIV (HUMAN IMMUNODEFICIENCY VIRUS) - Amin, Saeful (Jurnal Kesehatan Bakti Tunas Husada: Jurnal Ilmu-ilmu Keperawatan, Analis Kesehatan dan Farmasi, 2013)
Amprenavir drug is used as part of antiretroviral therapy that works against infection by HIV reproduction slows down in the body called a protease inhibitor enzymes protease can prevent job that acts like a chemical scissors. This enzyme cuts HIV raw materials into specific pieces needed to build a new virus. Protease inhibitors can damage these scissors so it could be inferred that our bodies will become more healthy for longer. Research has been carried out by using the application docking PLANTS 1.1, Co-Pendrivelinux, Marvinsketch, YASARA and Molegro Molecular Viewer (MMV). As for the value obtained on the Root Mean Square Deviation (RMSD) is 1,2993 with a value of analysis results against the original from the docking ligand-amprenavir -115,739 kkal, , to the analysis result of docking 6 derivatesof amprenavir compound derived from the closest to the original ligand or most potential is on amprenavir code J4A With the value of energy ties and on -123,423 kkal, amperenavir have a derivative of hydrogen bonds that equal to the original asp-25 , namely ligand asp-30 and gly-27 .Â Keyword: Amprenavir, docking, Anti-HIV Protease Inhibitor